Investigation of defects dependence of local piezoelectric response on Fe, La-modified (Pb,Sr)TiO3 thin films: A piezoresponse force microscopy study - Bastos, W. B.; Longo, E.; Chiquito, A. J.; Pontes, D. S. L. [UNESP]; Pontes, F. M. [UNESP] (Elsevier B.V., 2018)
In this study, undoped-(Pb,Sr)TiO3 and Fe3+, La3+ co-doped (Pb,Sr)TiO3 thin films were investigated at the nanoscale level by piezoresponse force microscopy (PFM), in order to evaluate the impact of doping induced damages on the ferroelectric and piezoelectric properties. Detailed investigations with nano scale resolution have revealed occurrence of abnormal domains in writing pattern under forward and reverse bias for (Pb,Sr,La)(Ti,Fe)O-3 thin films. Further piezoresponse hysteresis loop measurements show that fully switchable loops were observed under high voltage mediated by defect dipoles and by ferroelectric-like polar defects clusters. They have been discussed taking into account charged defect formation with both local changes in the dipole moment and local symmetry breaking effects. In addition, the domain writing and its retention behavior of the undoped-PST and (Pb,Sr,La)(Ti,Fe)O-3 thin films were investigated. Undoped-PST films exhibited better stability for both positive and negative domains for a relatively long time in comparison to that observed for (Pb,Sr,La)(Ti,Fe)O-3 films. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Point defects; Thin films; Piezoresponse force microscopy; Piezoelectric behavior